PENGEMBANGAN MEDIA AUDIO VISUAL RUMAH ADAT SELASO JATUH KEMBAR PADA MATA PELAJARAN IPAS DI UPT SDN 035 TARAI BANGUN - Rezi Andesta Putra; Erlisnawati; Hendri Marhadi (STKIP Subang, 2025)
This study aims to develop an audio-visual learning media on the Selaso Jatuh Kembar Traditional House as a learning resource for fourth-grade IPAS instruction that is valid, practical, and feasible to use. The research employed a Research and Development (R&D) approach using the 4D development model consisting of Define, Design, Develop, and Disseminate. The developed media was validated by three experts, namely a material expert, a media and design expert, and a language expert. In addition, its practicality was assessed through practicality questionnaires administered to teachers and students during limited trials. Data collection techniques included observation, interviews, documentation, and questionnaires. The validation results show that the audio-visual media achieved a very high level of validity, with expert scores of 96.66% for material, 85% for design, and 93.33% for language. The practicality results also indicate that the media is highly practical, with teacher practicality reaching 97.33%, one-to-one trial results at 89.20%, small-group trials at 87.99%, and real class trial results at 91,56%. These findings demonstrate that the media is easy to use, engaging, and effective in supporting classroom learning. Therefore, the audio-visual media on the Selaso Jatuh Kembar Traditional House is considered valid, highly practical, and suitable for IPAS instruction. It also enhances students’ understanding of local cultural heritage and supports the implementation of the Merdeka Curriculum by providing an engaging, meaningful, and contextually relevant learning experience for elementary school students.